Contribution of Occupational Therapy to funcional approach in personality disorders - Bellido Mainar, J R; Berrueta Maeztu, L M; Ariñez Merchán, I (Asociación Profesional Gallega de Terapeutas Ocupacionales (APGTO), 2004)
Personality disorders ( personality disorder F03.675 ) are defined by a rigid pattern of unadapting behaviours that, on the short and medium term generate a significant socio environmental deterioration. The level of psychosocial function or dysfunction is a first class indicator when assessing the extent and assessment of the personality disorder.Psychotherapy ( psychotherapy F04.754 ) intervenes in the psychosocial compounds of this disorder by designing specific programs for the training in psychosocial skills (conductual-dialectic therapy). Occupational Therapy ( occupational therapy E02.831.489 is a health science with a long history in socioenvironmental therapy of mental diseases F04.754.864 ) . The focal point is the assessment of the disease, disorder or social unadaptation impact in the individual's occupation functionality. This science puts forward a wide, integrating concept of functionality, which is divided into three occupation areas: productive occupational area, self maintenance area and leisure time area.In the first part of this paper, the extent and features of the occupational disfunction in the personality disorder are analysed employing the occupational therapy method.Based on our six-year experience, a method for socioenvironmental treatment based on two models of occupational therapy (human occupation model and Canadian model) is suggested in the second part of the paper